Impact of Physical Infrastructure and Technology on Student Learning Outcomes - Nurpaidah Nurpaidah; Muh. Yunus; Elpisah Elpisah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study was to determine the effect of physical and technological infrastructure on student learning outcomes at SDN 48 Tana Bacue Kec. Segeri Pangkajene and Islands Regency. Data collection using questionnaires, documentation, observation and interviews. The purpose of this study was to determine partially and simultaneously the effect of physical infrastructure and technology on student learning outcomes at SDN 48 Tana Bacue Kec. Segeri Pangkajene and Islands Regency. The results of the research that have been conducted show that the results of this study concluded that there is an influence of physical infrastructure and technology on student learning outcomes at SDN 48 Tana Bacue Kec. Segeri Pangkajene and Islands Regency. Likewise, there is an influence of the Technology variable on Student Learning Outcomes at SDN 48 Tana Bacue Kec. Segeri Pangkajene and Islands Regency. The results of this study concluded that Physical Infrastructure and Technology have a significant influence on Student Learning Outcomes at SDN 48 Tana Bacue Kec. Segeri Pangkajene and Islands Regency.